Estudo da viabilidade do resíduo proveniente das porcelanas de isoladores para utilização em concretos bombeáveis estruturais - Vieira, Flávio de Lima (2017)
This research aims to evaluate the tecniques for disposal of waste obtained from electrical insulators. These pieces are one of the supplies widely used for electric power generation, and become a waste due to their replacement for new ones after maintenance and expansion works, in places like substations, generating units, distribution networks, transmission lines and its own production process. In Brazil, it is possible to acumulate waste from these insulators in courtyards and waste areas, besides wastelands, impairing the environment. Thus, it is known that an alternative for treatment is needed and the lack of knowledge and techical safe forces the development of reasearches about this subject, what are still in the beggining. So, this study proposes the evaluation of potential use of such a porcelain in concrete, through the replacement of conventional aggregates and cement. The research was conducted with a careful characterization of the waste in different maximum dimension sizes, with physicochemical and mineralogical analysis obtained from X-Ray diffration and images from scanning eletronic microscopy, for example. Besides, tests of alkali-aggregate reaction were perfomed in order to assess the chemical stability of the waste in mortar. Regarding to viscoelastic and mechanical properties, the compressive strength, modulus of elasticity, water absorption, and abrasion/erosion were performed. The experimental program considered eleven different mixes of pumped concrete, take into account the following replacement rates: 8% replacement of cement; 50% and 100% replacement of fine aggregate; and 45% and 100% replacement of coarse aggregate. Some mixes were done with both replacement of fine and coarse aggregate. The investigation of mechanical strength, deformation and durability, in conditions aforementioned, demonstrates that concrete with replacement was statistically similar to concrete without any replacement by waste, resulting a suitable concrete with porcelain waste content. The efficiency of compressive strength ranged from 0,087 MPa/kg to 0,107 MPa/kg and the modulus of elasticity reached values up to 38 GPa, indicating expressive results for these properties. Lastly, in research is possible to observe the conclusions about reological characteristics of all concrete and the influence of these replacement on cement content.